FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT REPORT LAG PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Reynaldi; Rudi Setiadi Tjahjono (E-Jurnal Akuntansi TSM, 2022)
The purpose of this research is to obtain empirical evidence about the effect of profitability, auditor switching, corporate complexity, accounting firm reputation, board of director size, company size, ownership dispersion, and ownership concentration as independent variables to audit report lag as dependent variable. The population in this research is manufacturing companies that listed in Indonesia Stock Exchange (BEI) from 2018-2020. The sample used for this research consist of 78 listed manufacturing companies. The selection of these sample used the purposive sampling method with total 234 research data and the data analysis method in this research is used multiple regression analysis. The result in this research indicated that profitability had effect to audit report lag. While auditor switching, corporate complexity, accounting firm reputation, board of director size, company size, ownership dispersion, and ownership concentration had no effect to audit report lag